ANALISIS KEBUTUHAN RUANG PARKIR PARAGON MALL SEMARANG - Andreas Novier; Grace Simanjuntak; Y.I. Wicaksono; Amelia Kusuma Indriastuti (Jurnal Karya Teknik Sipil, 2015)
Paragon Mall Semarang is the one of the biggest shopping centers in Semarang City. Parking space has been provided since the beginning of mall’s area development, however it is no longer sufficient to meet the current demand. It is proved by the additional parking area in certain times, thus the effectivity of this parking area needs to be assessed more thoroughly. This Study aims to plan the parking space’s availability with sufficient capacity and to give recommendation in implemetation and development of parking space. Methodologies used include: calculation standart capacity based on current guidance, deviation of cumulative graph for calculating current need, space and tariff optimation, and future need calculation. Paragon Mall has 7 dedicated parking areas: 5 car parking areas and 2 motorcycle parking areas. At its peak hours, every area suffered space deficiency although there are some empty space in another parking area. Current parking space deficiency total of car area are only 10 SRPs and no deficiency in sepeda motor area. After optimation is done then the capacity is increased to 1115 SRPs of car and 2030 SRPs of sepeda motorcycle that is sufficient in the next 7 years or until year 2022. Tariff optimation is done to get progressive tariff therfore the visitors would not linger and eventually the space might serve more visitors. Space optimation on parking area layout and tariff should also be supported by management system. The overall amount of current parking space’s availibility shortage is 10 SRPs of car. After performing space and tariff optimization, the capacity is 1115 SRPs of car and 2030 SRPs of sepeda motorcycle that will last for the next 2 years i.e. up to 2017.Parking area’s layout of Paragon Mall Semarang with space and tariff optimization should also be supported by existing parking management system. Overall, Paragon’s parking area is only experiencing a minimum shortage.. To overcome the possibility of uneven accumulation in particular parking, solution that can be given is installing information panel which shows available parking space of all parking lot at the entrance to Paragon Mall Semarang.